2020
DOI: 10.1080/1331677x.2020.1862689
|View full text |Cite
|
Sign up to set email alerts
|

Workplace change within the COVID-19 context: a grounded theory approach

Abstract: The purpose is to investigate the current status and future evolution of the workplace within the COVID-19 pandemic context. Documents, publications and surveys from numerous sources have been analyzed to find out more about the employees' and organizations' experience with remote working and the advantages and disadvantages of accessing the workplace during the pandemic. The analysis of the data made possible the identification of patterns within the available literature regarding what has happened and, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 26 publications
(32 reference statements)
3
89
0
4
Order By: Relevance
“…We observe from Table 5 that COVID-19 deaths are causing unemployment in Italy and the UK. Our empirical results are in line with previous literature (Ancillo et al, 2020;Parvathamma, 2020;Couch et al, 2020;Fern andez-Villaverde & Jones, 2020;Blundell et al, 2020;Boneva et al, 2020;Fernandes, 2020). Our results show that COVID-19 cases are more cause of unemployment compared to COVID-19 deaths.…”
Section: Resultssupporting
confidence: 93%
“…We observe from Table 5 that COVID-19 deaths are causing unemployment in Italy and the UK. Our empirical results are in line with previous literature (Ancillo et al, 2020;Parvathamma, 2020;Couch et al, 2020;Fern andez-Villaverde & Jones, 2020;Blundell et al, 2020;Boneva et al, 2020;Fernandes, 2020). Our results show that COVID-19 cases are more cause of unemployment compared to COVID-19 deaths.…”
Section: Resultssupporting
confidence: 93%
“…Since this has developed into an extraordinary circumstance, the gig economy cannot keep up because of the current uncertainty (Umar et al 2020 ). The results show the importance of essential categories for rethinking the workplace after COVID-19 and for the whole process of change in the workplace (de Lucas Ancillo et al 2020 ). The service industry also suffers impacts from global foreign exchange markets volatility and uncertainty (Fasanya et al 2020 ).…”
Section: Literature Reviewmentioning
confidence: 85%
“…De Lucas Ancillo et al (2020) explain how the temptation to return to pre-COVID-19 approaches should be avoided. Instead, the best approach is to adopt methods that allow preventing mistakes previously made (de Lucas Ancillo, del Val Núñez and Gavrila, 2020). Furthermore, it is necessary to construct new frameworks for a digital world, educate, and prepare the organisation so that they can adapt to different work regimes and successfully blend between the processes related to face-to-face and remote work.…”
Section: Discussionmentioning
confidence: 99%
“…Such management concepts are competitive advantages, organisational capabilities, and sustainable performance. The studies investigating the academic, managerial issues have demonstrated how improved management theory can be applied to help maintain the functionality of higher education (Ghasemy and Hussin, 2014;Musingafi et al, 2014;Siegel and Leih, 2018). Academic managers (Department Heads) play pivotal roles in the management and governance of higher education institutions, making decisions that affect faculty careers, curriculum, student enrolments, and department budgets (Berdrow, 2010;Gmelch et al, 2017).…”
Section: Applied Management Theories In Higher Educationmentioning
confidence: 99%